Oxacillinase (OXA)-producing Acinetobacter baumannii in Brazil: clinical and environmental impact and therapeutic options - Micheli Medeiros; Nilton Lincopan (Sociedade Brasileira de Patologia Clínica, 2013)
Following a worldwide trend, infections caused by MDR OXA-type (Ambler class D) carbapenemase-producing Acinetobacter baumannii are currently regarded as a clinical and epidemiological emergency in Brazil. OXA-producing A. baumannii strains have been identified in the states of Alagoas, Amazonas, Bahia, Distrito Federal, Espírito Santo, Goiás, Mato Grosso, Mato Grosso do Sul, Minas Gerais, Paraná, Pernambuco, Rio de Janeiro, Rio Grande do Norte, Rio Grande do Sul, Santa Catarina and São Paulo. In some settings, the presence of OXA-23- and/or OXA-143 -producing A. baumannii (so far restricted to Brazil) has been endemic and A. baumannii strains carrying blaOXA-23 genes have been detected in hospital wastewater effluents, hence a potential risk to the community and the environment. Although molecular typing by multilocus sequence typing (MLST - Bartual scheme, University of Oxford, http://pubmlst.org/abaumannii/) has revealed the international spread of a clonal complex (CC) denominated CC92, in Brazil most OXA-23-producing A. baumannii belong to CC113, CC109 or CC104 clonal complexes. Finally, from a clinical point of view, the main problem of A. baumannii infections is the limited use of antibacterial agents with in vitro activity, often restricted to ampicillin/sulbactam, polymyxin B and/or colistin (polymyxin E).